Biochemical changes in affected potato tubers - S. Bomok; B. Taktaiev; M. Pikovskyi; O. Marieva (Карантин і захист рослин)
Goal. To establish biochemical changes (contents of dry matter, vitamin C, starch and carotene) in potato tubers in different degree affected by fungal diseases.